La Nouvelle-Orléans au XIXe siècle : femmes de couleur libres, femmes de pouvoir ? - Nathalie Dessens (Anglophonia)
This article dwells on the emergence of a few feminine figures in the studies conducted by historians of Louisiana since the 1980s and examines the relative invisibility of women in the early historiography of New Orleans’s antebellum period (1800-1860). Surprisingly at first sight, those women are almost all free Afro-Creole women. The object of the article is to explain the persistent—and even increased—celebrity of Marie Laveau, Henriette Delille, Juliette Gaudin, and Justine Couvent, as opposed to the silence surrounding their white counterparts of the same era. Concluding on the absence of "double jeopardy" in being black and a woman in nineteenth-century New Orleans, the article highlights Louisiana’s legal, social, economic, and cultural specificity in the antebellum South—and, more generally, in the nineteenth-century United States.